Organic exports from Madagascar - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Already one thousand Malagasy families work in organic agriculture, in family enterprises or on plantations, whether private or state owned. The total turnover in 1998 was estimated at E 2.3 million. A partnership has been set up with ECOCERT, a...